TINGKAT KEPEDULIAN MASYARAKAT PESISIR DALAM MELESTARIKAN FUNGSI HUTAN MANGROVE DAN HUTAN PAYAU DI DESA SUKABARU KABUPATEN KETAPANG - Ratnawati, Eni; Muin, Sudirman; Idham, M. (JURNAL HUTAN LESTARI, 2014)
society with mangrove forest ecosystem and brackish forest ecosystem that raises the existence of public awareness in preserving the function of mangrove forest and brackish forest. The method used is survey method with descriptive associative and used interview techniques with instrument a questionnaire. There are two types of data analysis namely  descriptive analysis used to see the general description characteristic of respondents and the level of public awareness and inferential analysis used to know different levels of income people who worked as fishermen and does not worked as fishermen by using independent sample t-test and  to know the factors that affect the level of public awareness by using multiple linear regression models. The level of public awareness coastal in preserving function mangrove forest and brackish forest is tend high. The results of independent sample t-test indicated there was no significant difference between the average income levels of  people who worked as fishermen with an average income levels of people who does not worked  as fishermen. Based on the analysis used multiple linear regression models was knowledge variables and cosmopolitan variables significantly influence the level of public awareness, while age variables, income variables, and perceptons variable were not significantly influence the level of public awareness. Keywords: The level of public awareness, mangrove forest, brackish forest